Mohammad Rasjidi dan Konstruksi Historis Oksidentalisme Indonesia - Trio Nurul Fajri Putra (UIN Sunan Gunung Djati Bandung, 2025)
The historical construction of Indonesian Occidentalism developed through critiques of Western epistemological and cultural hegemony, from the colonial period to post-independence. Mohammad Rasjidi (1915-2001) emerged as a key figure in shaping Indonesian Occidentalism, a framework critiquing Western dominance. This article aims to explore Rasjidi’s views on the West, his critiques of Orientalism and modernism, and his contributions to Indonesian Occidentalism within the global discourse on decolonizing knowledge. Using a qualitative approach with library research, this study analyzes Rasjidi’s primary works and relevant secondary sources through an interpretative-historical lens. The findings show that Rasjidi played an active role in constructing Indonesian Occidentalism by criticizing the secularization and moral relativism of the West, rejecting the unfiltered adoption of Western paradigms in Islamic studies, and using Western intellectual tools to critique the West itself as a protective strategy. Rasjidi’s ideas represent the defensive-polemic phase of Indonesian Occidentalism, laying the groundwork for more dialogical-academic generations like Mukti Ali and Nurcholish Madjid, enriching the Islamic perspective in the West-East relationship in a constructive and sustainable way